RESULTS OF THE STUDY OF OAT SOURCE MATERIAL IN THE ENVIRONMENTS OF ALTAI TERRITORY - N. V. Deines (Труды по прикладной ботанике, генетике и селекции)
Results of studying the oat collection of the N. I. Vavilov All-Russian Institute of Plant Genetic Resources are presented. Field and laboratory evaluation has been carried out to identify accessions which later will be used as source material for the development of promising breeding lines.